The lost children : the boys who were neglected - Goble, Paul (Bradbury Press ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1993)
A Blackfoot Indian legend in which six neglected orphaned brothers decide to go to the Above World where they become the constellation of the "Lost Children," or Pleiades.